Dissolution enhancement of glimepiride dispersion using glyceryl monostearate and ?-cyclodextrin as carrier (International Current Pharmaceutical Journal, 2015)
Glimepiride is an antidiabetic drug of sulfonylurea group and indicated for the treatment of type 2 diabetes mellitus. The present study was conducted to enhance the dissolution rate of glimepiride solid lipid nano particle dispersions using hot homogenization method and glimepiride solid dispersion by precipitation method. Solid lipid nanoparticles have been used as suitable carriers for delivery of drug with poor solubility. In this investigation glyceryl monostearate and stearic acid were used as solid lipid, Lutrol F-68 as surfactant, Tween 80 as stabilizer and the used polymer were urea crystal and ?-cyclodextrin. Three formulations were prepared in different ratios for two methods and were designated as GMLN1 to GMLN3 in case of hot homogenization method and GMP1 to GMP3 for precipitation method. The evaluation of all the dispersions were done by in vitro dissolution studies using US Pharmacopeia type II apparatus (paddle method) in 900ml distilled water at 50 rpm to a temperature of 37°C ± 0.5°C for 45 minutes. In situ and externally sink method revealed the release pattern of drug was found to follow zero order, first order and Korsmeyer-Peppas equations. Improved dissolution profile was observed in all the solid lipid nano particle dispersions as compared to pure drug as well as market preparation. Thus, glyceryl monostearate and ?-cyclodextrin can be successfully used as carrier for improvement of dissolution and bioavailability of glimepiride.Rafshanjani et al., International Current Pharmaceutical Journal, September 2015, 4(10): 436-441